2013
DOI: 10.3389/fpsyt.2013.00079
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstance Use in Cannabis Users Referred for Treatment: Drug Use Profiles, Psychiatric Comorbidity and Cannabis-Related Beliefs

Abstract: Background: Population-based surveys demonstrate cannabis users are more likely to use both illicit and licit substances, compared with non-cannabis users. Few studies have examined the substance use profiles of cannabis users referred for treatment. Co-existing mental health symptoms and underlying cannabis-related beliefs associated with these profiles remains unexplored.Methods: Comprehensive drug use and dependence severity (Severity of Dependence Scale-Cannabis) data were collected on a sample of 826 cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 43 publications
4
49
0
1
Order By: Relevance
“…The rare use frequency of the other substances rather indicates a pattern of experimentation, where future repeated use may not be anticipated. This pattern is consistent with the typical profile of PSU [8]. Nicotine use was the most frequently co-used substance but did not directly relate to any outcome.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The rare use frequency of the other substances rather indicates a pattern of experimentation, where future repeated use may not be anticipated. This pattern is consistent with the typical profile of PSU [8]. Nicotine use was the most frequently co-used substance but did not directly relate to any outcome.…”
Section: Discussionsupporting
confidence: 73%
“…A latent class analysis of 1,089 cannabis users from a community sample found that other illegal substance use occurred more often in the group with cannabis-related problems than in the nonproblematic users [15]. In a sample of 826 cannabis users referred for treatment, the highest severity of cannabis dependence, comorbid psychopathology, and dysfunctional cannabis cognitions was reported among those who additionally used a wide range of other substances; these other substances most often included amphetamines, and infrequently included tranquilizers and opiates [8]. Therefore, PSU and especially illegal substance use is associated with more severe CU-related problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La autoeficacia es una variable que, contradictoriamente, en estudios previos ha mostrado incrementos después de intervenciones (Blevins, Stephens, Walker, & Roffman, 2014;Connor et al, 2013;Hser, 2007;Wong & Longshore, 2008;Worley et al, 2014) y estabilidad que indica que la variable no es predictora del tiempo en abstinencia (Fiorentine & Hillhouse, 2003;Stein, Zane, & Grella, 2012). Los participantes de este estudio se mostraron con mayor autoeficacia en las evaluaciones post, sin interacción con el tipo de tratamiento que se brindó.…”
Section: Discusión Y Conclusionesunclassified
“…The early onset, heavy cannabis and polydrug use group in this study were found to experience the highest level of use-related problems, followed by the late-heavy-polydrug group. Similarly, Connor et al (11) report that, in a sample of adult cannabis users referred for treatment, those who engaged in polydrug use were more likely to be cannabis dependent and experiencing higher levels of comorbid psychopathology, than individuals who used cannabis, tobacco, and/or alcohol. Healey et al (12) also focused on a treatment sample, finding that both cannabis users and their clinicians reported difficulty in establishing a therapeutic bond.…”
mentioning
confidence: 99%